2018
DOI: 10.5045/br.2018.53.2.105
|View full text |Cite
|
Sign up to set email alerts
|

Busulfan plus melphalan versus high-dose melphalan as conditioning regimens in autologous stem cell transplantation for newly diagnosed multiple myeloma

Abstract: BackgroundHigh-dose melphalan (HDMEL) represents the standard conditioning regimen before autologous stem cell transplant (ASCT) in multiple myeloma (MM), but recent updates have suggested combination of melphalan with bulsulfan (BUMEL) is also associated with favorable outcomes. We performed the current study to address the lack of comparative studies between the two conditioning regimens in Asian populations.MethodsUsing the Korean National Health Insurance and Korean Health Insurance Review and Assessment S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Patients in the BUMEL-based group received conditioning regimen of busulfan plus melphalan in nine studies while received busulfan, melphalan plus bortezomib in one study. All the included studies had reliable quality as indicated by final scores of MINORS scale ranged from 16 to 19 for nine retrospective studies [ 12 14 , 25 31 ] (Additional file 2 : Fig. S1) and low risk for each item of Cochrane collaboration’s risk of bias tool for one RCT study [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients in the BUMEL-based group received conditioning regimen of busulfan plus melphalan in nine studies while received busulfan, melphalan plus bortezomib in one study. All the included studies had reliable quality as indicated by final scores of MINORS scale ranged from 16 to 19 for nine retrospective studies [ 12 14 , 25 31 ] (Additional file 2 : Fig. S1) and low risk for each item of Cochrane collaboration’s risk of bias tool for one RCT study [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent randomized controlled trial (RCT) demonstrated the encouraging results, which showed that the combination of busulfan plus melphalan 140 mg/m 2 (BUMEL) as pre-transplantation conditioning could achieve a significantly prolonged progression-free survival (PFS) compared with HDMEL 200 mg/m² [ 15 ]. According to several retrospective analyses, however, no difference of PFS was identified between MM patients having received conditioning of BUMEL and HDMEL [ 12 14 ]. Recognizing the controversial of data regarding BUMEL conditioning in MM patients having undergone upfront auto-HSCT, the present systematic review and meta-analysis was conducted to compare the efficacy and safety of BUMEL with those of HDMEL as the conditioning regimen for auto-HSCT in MM.…”
Section: Introductionmentioning
confidence: 99%
“…As explanation, occurrence of hepatic veno‐occlusive disease has been put forward (median appearance 29 days [range 3‐57] after ASCT) but it has also been suggested that PFS benefit was explained by Busulfan mechanism within bone marrow environment 14,15 . From 2016 onward, several teams have noted that adding Busulfan to the conditioning regimen offered a longer PFS in all‐risk groups of NDMM 16‐22 . Recently, a randomized prospective trial confirmed the PFS benefit for all‐risks patients in BuMel group vs Mel200.…”
Section: Discussionmentioning
confidence: 99%
“…15 Accordingly, KNHIS database has contributed to various epidemiological investigations into hematologic disease. [16][17][18][19][20] The study protocol is described in Figure 1. For patients in the primitive case and case cohorts, the index date was defined as the date of allo-SCT, whereas the index date was indicated as the year of participation in the public health checkup for individuals in the primitive control and control cohorts.…”
Section: Data Sourcementioning
confidence: 99%